Experimental protocol for bath infection of Atlantic salmon with Tenacibaculum dicentrarchi: Aiming for target mortalities - Imarai-Bahamonde, C; Benavides-Larenas, A (ELSEVIER, 2026)
Developing experimental protocols to establish infection models in fish is essential for identifying new and effective preventive tools to improve fish health and welfare. Tenacibaculosis, caused by Tenacibaculum species, is a significant concern, particularly for Atlantic salmon (Salmo salar). However, replicable infection models for studying this disease remain limited. In this study, we developed a reliable bath infection method for T. dicentrarchi, enabling targeted, controlled mortality rates. First, using flow cytometry, we accurately quantified viable bacteria that were subsequently used for bath infection. A consistent mortality of similar to 24 % was achieved across experiments, even when scaling up bath infection volumes. Infected fish displayed characteristic symptoms, including ulcers, oral erosions, and hemorrhages, and PCR confirmed bacterial presence. This protocol improved reproducibility in experimental infections with T. dicentrarchi, supporting research on new prophylactic methods and treatments against Tenacibaculosis.